Utilization of Rice Straw and Husk for Oyster Mushroom by Using Rice Spawn - Singh, Pankaj Kumar; Baboo, Akash; Singh, Pankaj Kumar (Indian Farming, 2022)
The experiment was carried out to investigate the utilization of rice straw and husk for oyster mushroom cultivation. This study was to evaluate the best alternative substrate (rice straw, rice husk, banana leaves, sawdust and maize dry leaves) that supports the growth of mushroom and produces the maximum yield. Data relating to the time taken for complete spawn running, pin head initiation, days to maturity of the fruiting bodies and total yield of the mushroom was recorded and analyzed. A total of six treatments replicated six times were taken under the complete randomized design. The minimum time taken for complete mycelium run was in (rice straw + maize dry leaves) and maximum time was taken in (rice straw + sawdust). Maximum yield was produced in (rice straw + maize dry leaves) and minimum in (rice + sawdust). The minimum time taken from primordial stage to harvesting stage in (rice straw +maize dry leaves) and maximum time was recorded in(rice straw + sawdust).Thus, it can be observed that rice straw and maize dry leaves substrates in combination proved to be best for the cultivation of oyster mushroom.